2012
DOI: 10.1021/om201189r
|View full text |Cite
|
Sign up to set email alerts
|

MCl2(ampy)(dppf) (M = Ru, Os): Multitasking Catalysts for Carbonyl Compound/Alcohol Interconversion Reactions

Abstract: The easily accessible complexes [MCl2(dppf)(ampy)] (M = Ru (cis-1), Os (trans-2); dppf = 1,1′-bis(diphenylphosphino)ferrocene; ampy = 2-aminomethylpyridine) in the presence of base (NaOiPr, KOtBu) are efficient catalysts for several reactions involving carbonyl compounds and alcohols. The derivatives 1 and 2 catalyze the selective transfer hydrogenation of aldehydes and ketones to alcohols with 2-propanol using 0.1–0.005 mol % of catalyst at 82 °C with TOF values up to 3.0 × 105 h–1. These compounds (0.1–0.02 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 75 publications
0
48
0
Order By: Relevance
“…In particular, given the good results obtained with the ruthenium-guanidinate derivatives A and B (Figure 1) in the redox isomerization of allylic alcohols, we ini- tially focused on this catalytic transformation. It should be mentioned at this point that, although the osmium complexes have been much less studied than the ruthenium complexes, [10] the recent work of Esteruelas [11] and Baratta [12] and their co-workers has demonstrated that efficient catalysts can also be obtained from this metal (TOF up to 460 h -1 ). However, the catalytic activities observed for 3a-m in the isomerization of the model substrate 1-octen-3-ol were very disappointing.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, given the good results obtained with the ruthenium-guanidinate derivatives A and B (Figure 1) in the redox isomerization of allylic alcohols, we ini- tially focused on this catalytic transformation. It should be mentioned at this point that, although the osmium complexes have been much less studied than the ruthenium complexes, [10] the recent work of Esteruelas [11] and Baratta [12] and their co-workers has demonstrated that efficient catalysts can also be obtained from this metal (TOF up to 460 h -1 ). However, the catalytic activities observed for 3a-m in the isomerization of the model substrate 1-octen-3-ol were very disappointing.…”
Section: Resultsmentioning
confidence: 99%
“…We recently prepared the derivative cis-RuCl 2 (dppf)(ampy) 18 (Scheme 10) which was found to catalyze a variety of organic transformations involving ketones and alcohols [18]. Treatment of RuCl 2 (PPh 3 ) 3 with 1,1-bis(diphenylphosphino)ferrocene (dppf) and Ampy in toluene at 50 • C gave in 92% yield the derivative 17 with trans-configuration, which by heating in toluene at reflux temperature for 24 h afforded the thermodynamically more stable cis-isomer 18 (Scheme 10) [19].…”
Section: Rumentioning
confidence: 99%
“…Treatment of RuCl 2 (PPh 3 ) 3 with 1,1-bis(diphenylphosphino)ferrocene (dppf) and Ampy in toluene at 50 • C gave in 92% yield the derivative 17 with trans-configuration, which by heating in toluene at reflux temperature for 24 h afforded the thermodynamically more stable cis-isomer 18 (Scheme 10) [19]. The Ru-complex 18 catalyzed efficiently the selective TH of aldehydes and ketones to alcohols [18]. By using a catalyst loading of 0.1-0.0005 mol% and in the presence of NaOi-Pr (2 mol%) in 2-propanol, quantitative conversion of several carbonyl compounds was achieved at 82 • C in a short time, affording TOF up to 1.0 × 10 5 h −1 (Scheme 11).…”
Section: Rumentioning
confidence: 99%
See 2 more Smart Citations